Preventive effect of Macaranga barteri Mül Arg. (Euphorbiaceae) aqueous leaf extract on amiodarone induced non-alcoholic fatty liver disease in rats (World Journal of Current Medical and Pharmaceutical Research, 2021)
Macaranga barteri is a plant used in traditional medicine to treat non-alcoholic fatty liver disease. However, its potential against hepatic steatosis has not been scientifically proven yet. This work aimed to investigate the preventive effect of the aqueous extract of Macaranga barteri leaves (AEMb) on hepatic steatosis experimentally induced with amiodarone in rats. 36 rats were divided into 6 groups of 6 rats each. Group 1, the non-intoxicated group and Group 2, used as controls were pretreated with distilled water (10 ml/kg b.w.). Group 3 received silymarin at 100 mg/kg b.w. while Groups 4, 5 and 6 were pretreated with AEMb at doses of 125, 250 and 500 mg/kg b.w. respectively. The weights of the rats were monitored during the experimentation. After 7 days of daily pretreatment with the different substances, rats of groups 2 to 6 were administered intraperitoneally amiodarone (200 mg/kg bw) three times daily for seven other consecutive days. At the end of the experiments, blood samples were collected on fasted and anesthetized rats kept in dried and EDTA tubes in order to assess some hematological and biochemical parameters and also rats livers were removed for gross observation and hepatic triglyceride assessment. The results revealed that AEMb and silymarin inhibited the weight loss induced by amiodarone and even favored weight gain. The reduction of heamatological indices (leukocytes and leukocyte indices, erythrocytes and erythrocyte indices (MCV, MCH and MCHC), hemoglobin, hematocrit and thrombocytes) by amiodarone was impeded in AEMb treated rats. AEMb significantly reduced (p